Analysis of the Effect of Fear of Missing Out, Sales Promotion, E-wallet on Impulse Buying on TikTok Shop Users at the Three Largest Universities in Purwokerto - Ramdhani, Muhamad Luthfi; Utami, Restu Frida; Astuti, Herni Justiana; Arofah, Rifka Utami (International Journal of Business and Applied Economics, 2025)
This study analyzes the influence of FoMO Sales Promotion, E-wallet on Impulse Buying on Tiktok Shop users at the three largest universities in Purwokerto. The object of this research is Tiktok Shop user students at the three largest universities in Purwokerto. This research is quantitative, the number of samples in this study were 130 respondents with the IBM SPSS version 25 analysis tool. FoMO and Sales Promotion have a positive and significant effect on Impulse Buying. Not all consumers make Impulse Buying. Not all consumers make Impulse Buying by transacting payments using E-wallet because there are other features on Tiktok Shop such as cash on delivery, virtual account transfers, then using a credit or debit card.